Decolorization of reactive black 5 from synthetic dye wastewater by fenton process - Sermpong Sairiam (2020)
© 2019, Thai Society of Higher Eduation Institutes on Environment. All Rights Reserved. Reactive Black 5 (RB5) is an azo dye commonly used in industries. Its toxicity and nonbiodegradability require an effective treatment process. In this study, the oxidation of RB5 wastewater by Fenton process was observed. The experiments were conducted with synthetic RB5 wastewater in a 1-liter batch reactor with a stirrer. The effects of initial ferrous (Fe2+) concentration and pH on RB5 removal were studied. The results showed high removal efficiency (>90%). Increasing the concentration of Fe2+ could increase the RB5 decolorization by Fenton process. The decline of of remaining Fe2+ let to the genertation hydroxyl radicals (•OH) from hydrogen peroxide (H2O2). The initial degradation rate of RB5 decolorization was increased from 0.0023 to 0.0754 mM/min. In contrast, the RB5 decolorization of RB5 was decreased when the pH was increased from 3 to 5. The optimal condition of the RB5 removal was determined as follows: pH 3, 5 mM of H2O2, and 0.5 mM of Fe2+. At this condition, the almost complete delorization of RB5 by Fenton process was achieved within 30 minutes.